PERAN BIMBINGAN DAN KONSELING KRISTEN DALAM MEMBENTUK KESEHATAN MENTAL DAN KARAKTER REMAJA DI ERA DIGITAL - Sriayu Buari'; Riantho Betteng Salong; Devita Noro' Palullungan; Melbin Palungan; Ristayani (CV. ADIBA AISHA AMIRA, 2026)
This study examines the role of Christian guidance and counseling in shaping the mental health and character of adolescents in the digital era. The development of digital technology has a significant impact on the lives of adolescents, both positively and negatively. Excessive use of social media, cyberbullying, internet addiction, and identity crises are challenges that affect the mental and moral condition of the younger generation. This study used a literature review method by reviewing various relevant scientific sources on mental health, adolescent character, and Christian counseling. The results show that Christian guidance and counseling play a crucial role in helping adolescents manage their emotions, build a positive self-concept, and shape character based on the values ​​of love, honesty, responsibility, and self-control. Furthermore, collaboration between family, school, and church is a crucial factor in supporting adolescents' mental and spiritual development. With appropriate guidance, adolescents can face the challenges of the digital era in a healthier, wiser, and more responsible manner.